Microbial Diversity Exploration of Marine Hosts at Serrana Bank, a Coral Atoll of the Seaflower Biosphere Reserve - Alvarez-Yela, Astrid Catalina; Mosquera-Rendón, Jeanneth; Noreña-P, Alejandra; Cristancho, Marco; López-Alvarez, Diana (Frontiers in Marine Science, 2019)
Microorganisms represent nearly 90% of ocean biomass and are fundamental for the functioning and health of marine ecosystems due to their integral contribution to biogeochemical cycles and biological processes. In marine environments, microorganisms exist as microbial communities in the water column, benthonic substrates and macroorganisms, where they establish symbiotic interactions and fulfil their ecological roles. Such interactions can have a harmful or beneficial impact on the hosts depending on the emergent properties of the communities, their taxonomic structure and functionality. To evaluate these features, culture independent approaches like metabarcoding have been developed and have hugely contributed to the characterization of marine microbial diversity. The present study was aimed to explore the structure and metabolic functionality of microbial communities associated to marine hosts at the Serrana Bank, a coral atoll part of the Seaflower Biosphere Reserve (Archipelago of San Andrés, Old Providence and Saint Catalina, Colombia). We found a highly diverse microbial assemblage associated with the corals Siderastrea siderea, Colpophyllia natans and Orbicella annularis, the sponge Haliclona sp. and sediment from Isla de los Pájaros lagoon. However, the coral Porites astreoides had significantly lower bacterial diversity and a different community composition. Proteobacteria was the most abundant phylum within bacterial communities in the evaluated hosts, except in P. astreoides, where Cyanobacteria was the predominant group. Firmicutes, Actinobacteria, Bacteroidetes, Acidobacteria, Chloroflexi and Gemmatimonadetes were also identified within all microbiomes, but their dominance varied between hosts. Additionally, the most abundant group among the fungi communities associated with O. annularis, S. siderea and C. natans was Ascomycota, but significant differences between clasess and order were observed among hosts. Finally, functional profiles revealed that the principal microbial functions were focused on membrane transport, carbohydrates, amino acids and energy metabolism, replication and translation processes. A significant higher metabolic functionality was found in the sponge microbiome in comparison to the coral microbial communities.